Representasi Pelacur Perempuan dalam Novel Re: karya Maman Suherman - Sri Devi Wahyu Ningsih; Yenni Hayati (Jurnal Bahasa dan Sastra, 2020)
The image of prostituted women always gets a negative stigma in society. Therefore, various studies are needed to understand the ins and outs and portraits of prostitutes in various literatures. This study aims to describe the representation of female prostitutes in Maman Suherman's Re:. This type of research is qualitative with descriptive methods. The data in this study are in the form of words, phrases, clauses, and sentences that indicate the representation of female prostitutes in the novel. The data source in this study is the novel Re: by Maman Suherman, published by Prima Grafika in Jakarta in 2014 which consists of 161 pages, which is the first printing. The findings in this study indicate that the representation of female prostitutes in Maman Suherman's novel Re: by Maman Suherman has several parts, (1) categories of female prostitutes, (2) types of representation of female prostitutes, (3) the background or motive for the representation of female prostitutes, and (4) due to representation of female prostitutes.